New Insights of Anti-Hyperglycemic Agents and Traditional Chinese Medicine on Gut Microbiota in Type 2 Diabetes - Chen Y; Wang M (Dove Medical Press, 2021)
Yanxia Chen, Mian Wang Department of Endocrinology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050051, People's Republic of ChinaCorrespondence: Mian WangDepartment of Endocrinology, The Second Hospital of Hebei Medical University, 215 Hepingxi Road, Shijiazhuang, Hebei, 050051, People's Republic of ChinaEmail wangmian66@sina.comAbstract: Type 2 diabetes mellitus (T2DM) is a widespread metabolic disease characterized by chronic hyperglycemia. Human microbiota, which is regarded as a "hidden organ", plays an important role in the initiation and development of T2DM. In addition, anti-hyperglycemic agents and traditional Chinese medicine may affect the composition of gut microbiota and consequently improve glucose metabolism. However, the relationship between gut microbiota, T2DM and anti-hyperglycemic agents or traditional Chinese medicine is poorly understood. In this review, we summarized pre-clinical and clinical studies to elucidate the possible underlying mechanism. Some anti-hyperglycemic agents and traditional Chinese medicine may partly exert hypoglycemic effects by altering the gut microbiota composition in ways that reduce metabolic endotoxemia, maintain the integrity of intestinal mucosal barrier, promote the production of short-chain fatty acids (SCFAs), decrease trimethylamine-N-oxide (TMAO) and regulate bile acid metabolism. In conclusion, gut microbiota may provide some new therapeutic targets for treatment of patients with diabetes mellitus.Keywords: gut microbiota, anti-hyperglycemic agents, traditional Chinese medicine, type 2 diabetes mellitus